Building Holistic Defense: The Design and Evaluation of a Social Work Centric Model of Public Defense. (July 2020) - Harris, Heather M.
Holistic defense is a model of public defense rooted in the early 20th century recognition that lawyers and social workers should cooperate to advocate with and for individuals and communities in need. Prior work on holistic defense highlighted its potential to transform the lives of public defender clients by transforming the legal practice of attorneys. Comparatively, social workers' roles in these transformations have been neglected. Yet many holistic defense programs begin by integrating social workers onto legal teams. In this article, I describe and evaluate a social work centric holistic defense model piloted in Santa Barbara, California. My research supports recent findings that holistic defense improves case outcomes and substantially reduces incarceration without negatively affecting public safety. I discuss my results in the context of prior research and the potential for holistic defense to reform criminal justice. I then make recommendations for the design of future holistic defense evaluations.